Calculations with the creditors in the event of termination of business entities by the example of the reorganization - Петров, Євген Вікторович; Белуга, Юлія Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The article is devoted to the defence of rights and ensuring the creditors’ claims satisfaction to the company in reorganization process. Defence of rights and ensuring the creditors’ claims satisfaction to the company in reorganization process is one of the most important problems of legal regulation and a guarantee of public economic order stability. The purpose of legislative regulation of such relations is to prevent restrictions of the contractors’ rights, as in practice the company is often ceased to avoid the full satisfaction of the contractors’ claims. The regulatory consolidation of the payment order between creditors and company in reorganization process should prevent such negative phenomena. In the article the payment order between creditors and company in reorganization process is analyzed. Apart, the authors noted that during reorganization of the company legislation does not constitutes the turn of satisfaction of the creditors’ claims, and it is a gap in legislation. The authors state that fixing the term of submission the creditors’ claims gives creditors additional guarantees, i.e. protect their interests, and in some way stabilize the debtor status giving the guarantees that claims will not be submitted the day before the end of reorganization. Also the end of such terms should not deprive the contractors their right to submit their claims. Accordingly, to the authors’ mind, the creditors should use part 6, article 112 of the Civil Code of Ukraine under law analogy if they missed deadline of submission the claims during reorganization. Also the authors research the following questions: how long the company should satisfy the creditors’ claims to terminate civil relations; is it possible for company to agree with the counterparties not to submit the claims on early performance of obligations, and if yes, under which conditions? They concluded that such claims should be satisfied throughout the period of reorganization, and even after ceasing the company by its successors.